2020
DOI: 10.28933/ajar-2019-09-2705
|View full text |Cite
|
Sign up to set email alerts
|

INCIDENCE AND SEVERITY OF ANTHRACNOSE (Colletotrichum lindemuthianum) ON SELECTED COMMON BEAN (Phaseolus vulgaris L.) GENOTYPES

Abstract: Common bean (Phaseolus vulgaris L.), is among the most important legume crop for protein source in peoples' diet globally and including Kenya. Anthracnose (Colletotrichum lindemuthianum) is a common disease of legumes that causes yield loss of upto 90-100%. Potential production of common beans in Kenya is expected to be above 2000 kg ha-1 but due to challenges of pests and diseases among them anthracnose, it remains below potential yields. The aim of the recent study was to investigate selected common bean gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
2
0
0
Order By: Relevance
“…Padder et al [ 13 ] and Masunga et al [ 7 ] reported similar findings, concluding that rainfall is an important environmental factor for the establishment, infection and development of common bean anthracnose. Significant anthracnose invasion was also reported by other authors [ 22 , 23 ] among common bean genotypes. AMMI analysis indicated that environmental main effect as the primary factor influencing anthracnose infection (58.9%) while genotype factor accounted for 32.7% anthracnose infection rate ( Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Padder et al [ 13 ] and Masunga et al [ 7 ] reported similar findings, concluding that rainfall is an important environmental factor for the establishment, infection and development of common bean anthracnose. Significant anthracnose invasion was also reported by other authors [ 22 , 23 ] among common bean genotypes. AMMI analysis indicated that environmental main effect as the primary factor influencing anthracnose infection (58.9%) while genotype factor accounted for 32.7% anthracnose infection rate ( Fig.…”
Section: Discussionsupporting
confidence: 85%
“…According to the ANOVA, there were significant differences (p≤0.05) in the severity of anthracnose infection both among the genotypes and environments. The significant genotype by environment interaction effect emphasizes the strong influence of the growing conditions on the expression of host resistance which is agreement with work conducted by Kiptoo et al (2020).…”
Section: Reaction Of French Beans and Differential Cultivars To Anthracnose Under Field Conditionssupporting
confidence: 89%